GERAKAN PETANI KENDENG DALAM MEMPERTAHANKAN KEDAULATAN PANGANNYA - Enkin Asrawijaya (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
Farmers in the Kendeng Mountains are traditional peasants who are very dependent on natural resources. They live by relying on the natural wealth of Kendeng as a local economic power. The life that is subsistence and relies on reciprocity norms makes it vital in solidarity against the forces of capitalism to defend food sovereignty. This research attempts to analyze from the perspective of postmodernism which views the practice of neoliberalism as destroying local farmers. The discussion shows that the emergence of the Kendeng farmer movement is due to the threat of environmental damage, which disrupts their livelihoods as farmers. The Kendeng peasant movement cannot be separated from actors from the Samin indigenous community who brought up the idea of resistance. The Kendeng Mountains Caring Community Network (JMPPK) is a movement organization capable of building resistance from grassroots movements to national-scale movements. Food sovereignty is one of the reporters for the movement so that kendang farmers get full access to exploiting the nature of Kendeng with their local wisdom so that the Kendeng mountains remain sustainable and protected from damage. Food sovereignty can be realized through food security, using the state giving freedom of rice field management without any intervention from disturbing investors.